Capacity analysis of the MEO satellite constellation - Ya-hui WANG; Hong-feng KUANG; Li-dong ZHU (Tongxin xuebao)
Aiming to calculate the system capacity of a given satellite constellation,a time-varying traffic model based on varying traffic with varying time zone was proposed.Focusing on a MEO satellite constellation with global coverage,using a load balanced routing algorithm,the system capacity in different time slices was analyzed and the effect of inter-satellite link (ISL) capacity on the system capacity was investigated.The time-varying traffic model makes analysis more reliable and effective via comparison with equal traffic model.Application of time slices reduces complexity of calculation.